Marx: política e emancipação humana (1848-1871) - Cotrim, Lívia Cristina de Aguiar (2007)
The purpose of this work is to inquire the relations between politics and human emancipation in Karl Marx s thought through immanent analysis of texts produced between 1848 and 1871 in which Marx focuses those subjects while examining remarkable historical events: articles written for New Rhine Gazette, published from June 1848 to May 1849; The Class Struggles in France, of 1850, The Eighteen Brumaire of Louis Bonaparte, of 1852, and The Civil War in France, including both of its Drafts, of 1871. This research shows that onto-negative determination of politics, found out by the author during the years when he constituted his own original thought, is maintained throughout the writings analyzed. That concept s development and concretization is also demonstrated through examining Marx s account on class struggles and political changes then taken place. In the first part of the research revolution and counter-revolution processes are approached within the never overcome German poverty, through New Rhine Gazette articles. In the second part, it is examined social revolution assertion in June 1848 insurrections, their defeat and Bonapartist state arousal. In both, forms of political actions and different classes consciousness elements were emphasized, as well as the relationships between classes and their political representations, their limits and potentialities. The third part focuses writings on Paris Commune understood as antithesis of the state, the non-state form of social emancipation. All the articles from New Rhine Gazette by Marx and those of unknown authorship were translated from the German originals and are presented as an appendix